PELAKSANAAN DISCHARGE PLANNING DI RUMAH SAKIT - Marliany, Heni; Permana, Yudhi; Permatasari, Intan (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
One of the nursing activities that have not been optimal now days is Discharge Planning. Discharge Planning in nursing is a related component  with a nursing range of patients admitted to hospital until his return. The purpose of this research is to determine on how the describing of discharge planning implementation in  inpatient care room of  hospital  CThis research is using descriptive method, the population of all nurses in the wards of RS.C 181 people. Obtaining sampling technique used is  proportional  random sampling. The research samples  is 64 nurses inpatient care room  in hospital CThe result of understanding  the most diseases are not carried out (96.9%). Explanations majority diseases cause categorical are not carried out (87.5%). Explanations sign and majority diseases simptom categorical are not carried out (90.0%). Explanations majority depelopment categorical is implementated (93.8%). Explanation of majority nutritions category is conducted as many as 61 respondents (95.3%). Explanation of activity and majority rest categorical is implemented  (90.6%). An explanation of the mobilization of the highest category is done (81.2%). Explanation giving majority motivation categorical  is conducted (95.3%). Explanation the majority control categorical is done (71.9%).Implementation of majority discharge planning categorical is done based on SPO (65.6%). It is expected that the hospital discharge planning is more concerned by providing the motivation on the nurse to perform appropriate discharge planning based on SPO. Keywords: Nurses, Implementation, Discharge Planning, Hospital